2018
DOI: 10.12913/22998624/92108
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Model Simulation of a Passenger Cable Car Operation

Abstract: Passenger ropeways represent an original and attractive way of transporting passengers. They are mainly deployed in mountainous conditions or urban agglomerations. In most cases, they are very closely linked to tourism. For their efficient operation and implementation of a wide range of analyses, various methods and approaches are used that differ from each other both in terms of results and input factors. Thanks to its options, the computer simulation method ranks among highly efficient tools. However, its us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…For cable cars to be reliable, cable car operators must maintain the quality and safety of the complete equipment [17,18]. All control work should be based on a proactive prediction of critical failures, using appropriate reliability models such as, for example, failure trees [19] or simulation models [20].…”
Section: Reliability Of the Cable Carmentioning
confidence: 99%
“…For cable cars to be reliable, cable car operators must maintain the quality and safety of the complete equipment [17,18]. All control work should be based on a proactive prediction of critical failures, using appropriate reliability models such as, for example, failure trees [19] or simulation models [20].…”
Section: Reliability Of the Cable Carmentioning
confidence: 99%
“…[3] In practice, applications have shown that the use of simulation can be widely used not only for business processes but also in such areas as transport simulation, where financial, material and personnel savings can be achieved. [4,6,10].…”
Section: Dynamic Simulationmentioning
confidence: 99%
“…Businesses have to learn to respond to their customers' demands very quickly, which can be, and often are, very specific, and which can often change with the environment and market expectations, revising legislation or sustaining society. In conjunction with Industry 4.0, dynamic simulations are being increasingly often used as an effective tool for optimizing a wide range of processes [4,12]. Especially the automotive industry is an area where the use of simulations already belongs to common practice [5].…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al [11], Jung et al, [12]) to assess the significance of this impact. However, they simulated only "conventional" construction processes using conventional cranes and other conventional construction machinery [13][14][15].…”
Section: Current Situation In the Field Of Simulation Modeling In Thementioning
confidence: 99%